The effect of short-term fallowing on the microbial communities in forest soil cultivated with ginseng: Preliminary research - Yuqing Li; Feyisike Gbolayori Jones; Bing Zhang; Juntao Cui; Wei Zhang (PeerJ, 2023)
Background Continuous cultivation of ginseng crops in fixed plots can lead to disease outbreaks, yield losses and replanting failures. Fallow periods can help restore soil health and increase the sustainability of agricultural systems; however, taking land out of production for extended periods is often not feasible. Short-term fallow periods could restore soil health, but few studies have examined the effects of short-term fallow treatment on the health of soil in ginseng fields. Methods In this preliminary study, we used metagenomic analysis to assess changes in the abundance of major ginseng pathogens and soil health overall following a short-term fallow period in a region in the Changbai Mountains. A sample from a forest plot (Hx0ks), was compared to a sample from a field where ginseng was previously cultivated and then had been left fallow for two years (Hx2), and a sample from a field that had been fallow for two years and was subsequently replanted with ginseng (Clsd). Results Soil that was fallow for two years, and then replanted with ginseng, showed reduced nutrient content and lower diversity of soil bacterial and fungal communities than soil that remained fallow. Candidatus Solibacter (5%) and Rhizomicrobium (3%) were the most abudant bacterial genera in Hx2. Rhizomicrobium (4%) and Gemmatimonas (3%) were the most abundant bacterial genera in Clsd. Mortierella (22%) and Peziza (12%) dominated the fungal community in Hx2. Lecanicillium (38%) and Mortierella (13%) dominated the fungal community in Clsd. Fallow periods also increased the functional diversity of soil as predicted by PICRUSt and decreased the relative abundance of the pathogenic fungi. Conclusions Preliminary findings were consistent with the hypothesis that fallow management in ginseng cultivation can improve soil microbial community structure and function and reduces the number of plant pathogens; however, testing this hypothesis will require replicated plots.